An electron microscopic method for the mapping of proteins attached to nucleic acids. - Wu, M (1978)
An electron microscopic method for demonstrating the presence of and mapping the positions of proteins specifically bound to nucleic acids is described. The nucleic acid-protein complex is treated with dinitrofluorobenzene under conditions such that dinitrophenyl (DNP) groups are attached to nucleophilic groups on the protein, with only a low level of random attachment to the nuclei acid. This product is treated with rabbit anti-DNP IgG. The position of the protein-(DNP)n(IgG)m complex on the nucleic acid strand can be observed by electron microscopy by protein free spreading methods and, in many cases, by cytochrome-c spreading. If necessary for visualization by the latter method, the size of the labeled region can be increased by treatment with goat anti-rabbit IgG. High efficiency of electron microscopic labeling is achieved. Examples studied are: the adenovirus-2 DNA terminal protein, a protein covalently bound to SV40 DNA, DNA polymerase I bound to DNA, E. coli RNA polymerase bound to T7 DNA, and proteins UV crosslinked to avian sarcoma virus RNA.